Transmisi dan Motif Pengajian al-á¸¤ikam Ibn Aá¹Äâ€™ Allah al-SakandarÄ« di Pesantren Tambak Beras Jombang - Mas?ud, Ali (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
The article seeks to reveal the transmission and motive of Ibn A??? Allah al-Sakandar??s al-?ikam recitation in Pesantren Tambakberas Jombang under the guidance of KH. Jamaludin Ahmad. This study employs quantitative and qualitative methods. The qualitative method is used to describe the pattern of transmission of al-?ikam which has been carried out at Pondok Pesantren Tambakberas, while the quantitative one is intended to measure the perceptions of those involved in the recitation of the book in regard with Sufism and political motives that colored the transmission process. Non-parametric inferential statistics are used to measure such perceptions of motives. The recitation of al-?ikam constantly transforms the values of Sufism onto the pupils. It can be seen, for instance, within the illustration of such Sufism doctrines as seeking and earning money from lawful occupation, self-restraint from temptations of the world, helping other people, giving charity for the seek of God to face the hereafter life, prohibition of lavish life as it will be the greatest temptation to gain God?s blessing, performing continuous and sincere repentance (tawbah na???), leaving any unlawfully vague matters (shubh?t), and living independently and abstinence-begging.